2013
DOI: 10.1089/apc.2012.0402
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Predicts All-Cause Mortality in Persons with Human Immunodeficiency Virus

Abstract: We examined the association between metabolic syndrome (MS) and its individual defining criteria on all-cause mortality in human immunodeficiency virus (HIV)-infected persons. We used data from 567 HIV-infected participants of the Nutrition for Healthy Living study with study visits between 9/1/2000 and 1/31/2004 and determined mortality through 12/31/2006. MS was defined using modified National Cholesterol Education Program guidelines. Cox proportional hazards for all-cause mortality were estimated for baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 33 publications
1
20
3
Order By: Relevance
“…In fact, aging is related not only with an increased incidence of renal disease but also with an increased incidence of other comorbidities. 16 However, in contrast with findings reported elsewhere, [13][14][15] viral load was not associated with an increase in the risk of kidney disease or proteinuria in our study, probably because of the viral suppression and preserved immune status (a protective factor) recorded in the most of our patients, which reduced the impact of HIV-related factors on renal alterations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In fact, aging is related not only with an increased incidence of renal disease but also with an increased incidence of other comorbidities. 16 However, in contrast with findings reported elsewhere, [13][14][15] viral load was not associated with an increase in the risk of kidney disease or proteinuria in our study, probably because of the viral suppression and preserved immune status (a protective factor) recorded in the most of our patients, which reduced the impact of HIV-related factors on renal alterations.…”
Section: Discussioncontrasting
confidence: 99%
“…[13][14][15] As is usual in several co-morbidities, age is a factor at risk to developed or worsened renal disease. 16 Renal disease has several clinical manifestations, from subclinical forms of renal damage, to decreased GFR or renal failure at end stages. 11 On the other hand, the relevance of renal damage in the HIV-infected population can be seen in the independent association between microalbuminuria and AIDS-related death (HR, 2.3; 95%CI, 1.3-4.3).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that AZT substitution is related to the patient's age, sex, clinical stage, hemoglobin levels and HIV transmission route. [4][5][6] However, there is A longitudinal study of AZT substitution has not been conducted in district level ART services in Indonesia. Given the relatively high incidence of AZT substitution and the impact treatment side effects can have on a person's quality of life, this study aimed to use longitudinal data from a public HIV treatment hospital in Indonesia to determine the risk of AZT substitution and the factors associated with it in HIV/AIDS patients starting AZT based ART.…”
Section: Introductionmentioning
confidence: 99%
“…MetS increases the risk for development of CVD, T2D, cardiovascular mortality, and all-cause mortality. The Nutrition for Healthy Living (NFHL) study analyzed data from 567 subjects and found that MetS and high triglycerides were associated with an increased risk of death after 36 months of follow-up [4]. It is very important to screen HIVinfected patients for MetS and address all nutrition-related causes.…”
Section: Nutritionmentioning
confidence: 99%